A dendronised polymer architecture breaks the conventional inverse relationship between porosity and mechanical properties of hydrogels. Issue 6 (23rd December 2020) - Evans, Cameron W.; Ho, Diwei; Lee, Peter K. H.; Martin, Adam D.; Chin, Ian L.; Wei, Zhenli; Li, Hua; Atkin, Rob; Choi, Yu Suk; Norret, Marck; Thordarson, Pall; Iyer, K. Swaminathan
Abstract : We present a series of synthetic polymer hydrogels which break the traditional correlation between pore size and mechanical properties. Abstract : We present a series of synthetic polymer hydrogels which break the traditional correlation between pore size and mechanical properties. The hydrogels are prepared from a dendronised polymer architecture based on a methacrylate copolymer to which poly(amido amine) dendrons are attached. Our approach will be useful in tailoring hydrogels for tissue engineering, controlled drug release, and flexible electronics.